2008
DOI: 10.3233/bd-2008-29110
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Nodal and Cripto-1: From Embryogenesis to Breast Cancer Progression

Abstract: Breast carcinoma cells and embryonic progenitors similarly implement stem cell-associated signaling pathways to sustain continued growth and plasticity. Indeed, recent studies have implicated signaling pathways, including those associated with the Notch, and Transforming Growth Factor-Beta (TGF-β) superfamilies, as instrumental to both embryological development and breast cancer progression. In particular, Nodal, an embryonic morphogen belonging to the TGF-β superfamily, and its co-receptor, Cripto-1, are requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 93 publications
3
53
0
Order By: Relevance
“…Recently, we have shown that Nodal and its receptors, activin receptor-like kinase 7 (ALK7) and ALK4, are expressed in human ovarian cancer cells . Furthermore, Nodal was also detected in rat ovarian follicular cells, normal and malignant human endometrial cells (Papageorgiou et al, 2009), lactating mammary (Kenney et al, 2004) and breast cancer cells (Strizzi et al, 2008), as well as islet cells in the pancreas (Zhang et al, 2008). The expression of Nodal in a variety of tissues suggests the extension of its biological function beyond embryo development.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, we have shown that Nodal and its receptors, activin receptor-like kinase 7 (ALK7) and ALK4, are expressed in human ovarian cancer cells . Furthermore, Nodal was also detected in rat ovarian follicular cells, normal and malignant human endometrial cells (Papageorgiou et al, 2009), lactating mammary (Kenney et al, 2004) and breast cancer cells (Strizzi et al, 2008), as well as islet cells in the pancreas (Zhang et al, 2008). The expression of Nodal in a variety of tissues suggests the extension of its biological function beyond embryo development.…”
Section: Introductionmentioning
confidence: 94%
“…Over-expression of Nodal in poorly-invasive cell lines in vitro led to an increased aggressiveness, while knocking-down Nodal in highlyinvasive cell lines exhibited an opposite effect. Many recent studies have proven the promoting effect of Nodal on tumor growth [12][13][14][15]. Lee et al [11] showed that Nodal over-expression increased the secretion of MMP-2, enhanced cell invasiveness, and promoted cell proliferation in vitro, as well as increased tumor growth in vivo.…”
Section: Introductionmentioning
confidence: 98%
“…Netrin-1 appears to be primarily expressed in regions of tissue remodelling rather than in quiescent tissue (Strizzi et al 2008). Interestingly, the ovarian follicle is a typical site of differentiation and reorganization 70 KD Fig.…”
Section: Discussionmentioning
confidence: 95%